Effects of physical activity dose on cognitive ability in Chinese adolescent students: parallel mediating roles of sleep quality and smartphone addiction - Li, Keqiang; Wang, Qianjin; Li, Jianye (Frontiers in Psychology, 2025)
IntroductionAdolescence is a critical developmental period marked by heightened vulnerability to cognitive and psychological disruptions. Although physical activity has been linked to improved mental health and cognition, the underlying behavioral mechanisms remain insufficiently explored. This study investigated the associations between physical activity and cognitive failures in adolescents, with sleep quality and smartphone addiction examined as parallel mediators.MethodsA cross-sectional survey was conducted among 522 adolescents (Mean age = 15.52, SD = 1.28), who completed validated questionnaires assessing physical activity (IPAQ-SF), sleep quality (PSQI), smartphone addiction (SAS-SV), and cognitive failures (CFQ).ResultsStructural equation modeling revealed that higher physical activity levels were associated with fewer cognitive failures, both directly and indirectly through better sleep quality and lower smartphone addiction. Group comparisons further indicated that adolescents with high physical activity reported significantly better sleep, reduced smartphone dependence, and fewer cognitive lapses compared to those with moderate or low activity levels. Correlational analysis supported these associations.DiscussionModerate or low activity levels. Correlational analysis supported these associations. Although causal inferences cannot be drawn due to the study’s cross-sectional design, the findings suggest that physical activity may be linked to improved cognitive functioning through modifiable behavioral factors. These results provide a foundation for future longitudinal and intervention-based research aiming to enhance adolescent cognitive health through lifestyle-based strategies.